Immunomodulatory effects of hydatid antigens on mesenchymal stem cells: gene expression alterations and functional consequences - Wang, Xin; Mijiti, Wubulikasimu; Yi, Zhifei; Jia, Qiyu; Ma, Junchao; Xie, Zengru (Frontiers in Microbiology, 2024)
Cystic echinococcosis, caused by the larval stage of Echinococcus granulosus, remains a global health challenge. Mesenchymal stem cells (MSCs) are renowned for their regenerative and immunomodulatory properties. Given the parasite's mode of establishment, we postulate that MSCs likely play a pivotal role in the interaction between the parasite and the host. This study aims to explore the response of MSCs to antigens derived from Echinococcus granulosus, the etiological agent of hydatid disease, with the hypothesis that exposure to these antigens may alter MSC function and impact the host's immune response to the parasite. Methods MSCs were isolated from mouse bone marrow and co-cultured with ESPs, HCF, or pLL antigens. We conducted high-throughput sequencing to examine changes in the MSCs' mRNA expression profile. Additionally, cell cycle, migration, and secretory functions were assessed using various assays, including CCK8, flow cytometry, real-time PCR, Western blot, and ELISA.Our analysis revealed that hydatid antigens significantly modulate the mRNA expression of genes related to cytokine and chemokine activity, impacting MSC proliferation, migration, and cytokine secretion. Specifically, there was a downregulation of chemokines (MCP-1, CXCL1) and pro-inflammatory cytokines (IL-6, NOS2/NO), alongside an upregulation of anti-inflammatory mediators (COX2/PGE2). Furthermore, all antigens reduced MSC migration, and significant alterations in cellular metabolism-related pathways were observed.Hydatid disease antigens induce a distinct immunomodulatory response in MSCs, characterized by a shift towards an anti-inflammatory phenotype and reduced cell migration. These changes may contribute to the parasite's ability to evade host defenses and persist within the host, highlighting the complex interplay between MSCs and hydatid disease antigens. This study provides valuable insights into the pathophysiology of hydatid disease and may inform the development of novel therapeutic strategies.